Influence Of Creep Law Form On Predicted Deformations In Salt - Ralph A. Wagner; Kirby D. Mellegard; Paul E. Senseny (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Six creep laws for salt, each fitted to the same laboratory data base, are used in a numerical model of the deformation of an opening in salt to determine the influence of creep law form on the predicted closures. Results show that predicted closures can be very sensitive to the functional form of the creep law chosen to model the laboratory data.